Nonglandular prickle formation is associated with development and secondary metabolism‐related genes in Rosa multiflora. Issue 3 (11th August 2021) - Zhang, Yu; Zhao, Mingjie; Zhu, Wan; Shi, Chunmei; Bao, Manzhu; Zhang, Wei
Abstract: Roses are among the most economically important ornamental plants worldwide. But prickles on the stem and leaves cause difficulties for cultivation or inconveniences during harvest and transportation, thus are an undesirable horticultural character. However, little is known about the molecular mechanisms of prickle development. In this study, we sought to develop Rosa multiflora (in the family Rosaceae) as a model plant to study prickle formation. The morphology, structure, and ontogeny of prickles were characterized, and transcriptome analysis of prickly and prickleless R. multiflora genotypes was performed. Morphological observation and microscopic analyses revealed that prickles of R. multiflora were non‐glandular prickles (NGPs) and their maturation went through five developmental stages, which was accompanied by the accumulation of secondary metabolites such as lignin and anthocyanins. Comparative transcriptome analysis identified key pathways and hub genes potentially involved in prickle formation. Interestingly, among the differentially expressed genes (DEGs), several notable development and secondary metabolism‐related transcription factors (TFs) including NAC, TCP, MYB, homeobox, and WRKY were up‐regulated in prickly internodes. KEGG enrichment analysis indicated that DEGs were enriched in the pathways related to biosynthesis of secondary metabolites, flavonoids, and phenylpropanoids in the prickly R. multiflora . Our study provides novel insights into the molecular network underlying the regulation of prickle morphogenesis in R. multiflora, and the identified candidates might be applied to the genetic improvement of roses.